Analisis Penerjemahan Indonesia-Arab Google Translate dan CHAT-GPT di Tinjau dari Linguistik Struktural dan Semantik - Setyawan, Cahya Edi; Zulaeha; Rauhillah, Siti; Mu’at (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study originates from the increasing use of artificial intelligence-based translation tools such as Google Translate and Chat-GPT in translating culturally embedded texts like Indonesian proverbs. The research focuses on the comparative analysis of translation outputs from both tools, particularly in the context of translating 26 selected Indonesian proverbs into Arabic. The objective is to evaluate how well each tool captures both the structural and semantic aspects of these culturally nuanced expressions. Using a qualitative descriptive method, the translations were analyzed through the lens of structural and semantic linguistics. The analysis revealed that while Google Translate tends to render literal translations that often fail to convey idiomatic or metaphorical meanings accurately, Chat-GPT demonstrates a higher capability in interpreting and contextualizing the intended meanings of the proverbs. The findings highlight a significant difference in the depth of linguistic and cultural understanding between the two tools, with Chat-GPT showing greater effectiveness in semantic adaptation. This suggests that AI-powered conversational models can provide more contextually appropriate translations, particularly for texts rich in cultural values. The study concludes that linguistic intelligence, especially in semantic interpretation, is crucial in achieving meaningful cross-lingual translation of idiomatic expressions.